O cotidiano como utopia: novas relações de espaço e tempo no mundo da arte contemporânea - Ana Carolina Freire Accorsi Miranda (Ciências Sociais Unisinos)
This paper investigates how utopia is a recurring term in the contemporary art world. The spread of collaborative relations - through art collectives, artistic residences, artivism - and the valorization of these practices by institutions afterwards is a frequent process in the art world today. In this paper I will discuss the discourse produced by artists, curators and theorists, thinking if these artistic practices in the world of contemporary art can work as a representation of the way in which contemporary culture has established its relationship with time and space. The hypothesis that I sustain here is that we live in a scenario where the art world valorizes collective artistic experiences that are associated with everyday aesthetics and afterwards classify it as a new utopia. A new temporality seems to emerge in the present culture, along with this, different utopian discourses rise in art. This type of art places itself as the utopia of the everyday life, constructed for the present time in the urban space. Thus, the focus of this paper is to make a brief theoreti- cal study on contemporaneity which points to important changes in the way in which individuals relate to everyday experience, narrative and memory, in order to understand the recent transformations in the world of contemporary art.